Book Review: “Factors Influencing the Research Productivity of Academics in Vietnam” by Dr. Nguyen Huu Quy (University of Foreign Language Studies - The University of Danang) (Journal of Contemporary Educational Policies and Practices, 2024)
Research is key to innovation and development of a country. Research is often a core component of a contemporary university, together with teaching and learning and services. Research productivity is also integral to university ranking and reputation.What are the key enabling and inhibiting factors to the research productivity of academics?This is a burning question that universities across different regions of the world are trying to answer.Dr Nguyễn Hữu Quý’s book entitled Factors Influencing the Research Productivity of Academics in Vietnam, published by the Vietnam Education Publishing House addresses the above crucial question in the context of Vietnam.